2019
DOI: 10.1186/s12940-019-0520-4
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air pollution is associated with pediatric pneumonia: a time-stratified case–crossover study in an urban area

Abstract: Background Pneumonia, the leading reason underlying childhood deaths, may be triggered or exacerbated by air pollution. To date, only a few studies have examined the association of air pollution with emergency department (ED) visits for pediatric pneumonia, with inconsistent results. Therefore, we aimed to elucidate the impact of short-term exposure to particulate matter (PM) and other air pollutants on the incidence of ED visits for pediatric pneumonia. Methods PM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 45 publications
6
33
1
6
Order By: Relevance
“…Meteorological factors such as daily temperature, relative humidity, and atmospheric pressure were adjusted in all models. The hysteresis effect of atmospheric pollutants has been con rmed by previous studies [22]. So, we chose the day of hospital visits (lag0) and subsequent six days (lag1-lag6) to assess the effect of air pollutants.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Meteorological factors such as daily temperature, relative humidity, and atmospheric pressure were adjusted in all models. The hysteresis effect of atmospheric pollutants has been con rmed by previous studies [22]. So, we chose the day of hospital visits (lag0) and subsequent six days (lag1-lag6) to assess the effect of air pollutants.…”
Section: Discussionmentioning
confidence: 88%
“…In terms of age strati cation, infants less than 1-year-old were proved to more sensitive to PM 2.5 and PM 10 in a study [13]. Cheng et al [22] found children older than four years were more vulnerable to PM 2.5 than those younger than four years. In this study, we found that children younger than four years old seem more susceptible to atmospheric pollutants.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Bacteria, viruses and mycoplasma are common pathogens that cause infantile pneumonia (IP) [2]. In recent years, with the changes in the environment and the abuse of antibiotics, the incidence of IP has continued to increase and the clinical symptoms are diverse [3,4]. If not treated in time during acute attack, it can cause serious damage to the respiratory system and other systems, even organ dysfunction [5].…”
Section: Introductionmentioning
confidence: 99%
“…As the environmental atmosphere gets more crowded and polluted without using clean fuels or technologies, the air that we breathe becomes dangerously polluted and cause kills for millions people around the world every year because of stroke, lung cancer and heart disease. Air pollution can penetrating deeply into our respiratory and circulatory system causing damaging to our lungs, heart and brain [1][2][3][4]. One of the main air pollution reasons is industrial processes and traffic.…”
Section: Introductionmentioning
confidence: 99%